Identifying the socio-economics of pantomime through Cinderella's footwear in 2017‐18 adaptations of the tale. Issue 1 (1st June 2019) - King, Sally
Footwear plays a significant role in the fairy tale Cinderella and in different versions of the tale the eponymous character's slipper has taken many different forms. Meanwhile, pantomime producers have for centuries been turning to the Cinderella tale for their stage adaptations, during which time the pantomimic slipper has regularly been described as a glass slipper, drawing on Charles Perrault's 1697 French version of the tale. The glass slipper has also become the most popular form in literature, film and other media, particularly under the influence of Disney. This said, the description does not accurately reflect the physical form of Cinderella's footwear in modern pantomime performances, which tends to be silver, sparkling, high-heeled shoes. Yet despite this general uniformity in the colour, style, size and material of Cinderella's slipper presented in pantomimes, each theatre and production company shade their depiction with different nuances. This distinction is achieved through the handling of the slipper in the performance proper, through scripting and mise-en-scène, and through the framing of the slipper in paratextual material, such as programmes, flyers, posters, promotional videos, publicity shots, reviews and exhibitions. Research into this material through document analysis and live spectatorship suggests that the depiction of the slipper is intertwined with identity, specifically the socio-economic identity of each theatre and production. Based on a sample of six Cinderella pantomime productions from the 2017‐18 season, it appears that Cinderella's slipper works to prime and satisfy audiences attending different types of pantomimes. In this way, footwear bolsters each theatre's self-identification and distinction from others whether they be small or large, recently founded or long-established, locally oriented or inflected by mass-media popular culture, in-house or commercially produced. Financial limitations or extravagance are encoded in the shoes, even when they appear almost identical upon cursory glance.